Multidimensional profiles of parent involvement: Antecedents and impact on student engagement. (24th August 2021) - Chan, Melvin; Manzon, Maria; Hong, Helen; Khong, Lana Y. L.
Abstract : Background: Parent involvement in school is a consistent predictor of educational success. However, research has been inconsistent in addressing how parent involvement ought to be defined and measured, which has led to varied findings across schools and educational systems. Aims: Attending to the multidimensionality of the construct, this study adopted a person‐centred approach to identify subpopulations of school‐based parent involvement. Subsequently, profile differences were investigated in relation to student engagement and three antecedent variables (gender, socio‐economic status, and authoritative parenting). Sample: Data were obtained from primary (10‐year old; N  = 4, 284) and secondary (14‐year old; N  = 3, 346) school students in Singapore. Methods: Latent profile analysis was conducted on student‐rated surveys of multiple parent involvement behaviours in school and their perceptions. Subsequently, the manual BCH method was employed to concurrently model covariates and outcomes on the latent profile model. Pairwise comparisons between profiles were examined for statistical significance. Results: Consistent across both cohorts, four distinct profiles emerged that revealed high, moderate, selective, and low parent involvement patterns. High parent involvement reflected high ratings across multiple activities, combined with positive perceptions of parental involvement. These profiles differed significantly in terms of their antecedent characteristics, particularly, authoritative parenting, and in relation to their impact on student engagement. Conclusion: Results from this study clarify relations between multi‐faceted dimensions of parent involvement in school. Additionally, there is a case for continued school‐family partnerships among secondary students as students remain academically engaged when parents are involved in school and students relate positively to their involvement.